MOORE–PENROSE INVERSE OF BIDIAGONAL MATRICES. IV - Hakobyan, Yu.R.; Aleksanyan, S.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
The present work completes a research started in the papers [1–3]. Based on the results obtained in the previous papers, here we give a definitive solution to the problem of the Moore–Penrose inversion of singular upper bidiagonal matrices.